Dihydroorotate dehydrogenase in oxidative phosphorylation and cancer - Boukalova, Stepana; Hubackova, Sona; Milosevic, Mirko; Ezrova, Zuzana; Neuzil, Jiri; Rohlena, Jakub (Biochimica et biophysica acta. Molecular basis of disease, 2020)
Dihydroorotate dehydrogenase (DHODH) is an enzyme of the de novo pyrimidine synthesis pathway that provides nucleotides for RNA/DNA synthesis essential for proliferation. In mammalian cells, DHODH is localized in mitochondria, linked to the respiratory chain via the coenzyme Q pool. Here we discuss the role of DHODH in the oxidative phosphorylation system and in the initiation and progression of cancer. We summarize recent findings on DHODH biology, the progress made in the development of new, specific inhibitors of DHODH intended for cancer therapy, and the mechanistic insights into the consequences of DHODH inhibition.
Keywords: Neoplasms; nádory; Ubiquinone; mitochondrie; Enzyme Inhibitors; proliferace buněk; ubichinon; Humans; lidé; oxidativní fosforylace; Oxidative Phosphorylation; Mitochondria; Oxidoreductases Acting on CH-CH Group Donors; oxidoreduktasy působící na CH-CH vazby; inhibitory enzymů; Electron Transport; transport elektronů; Cell Proliferation